Command of a 2-D cursor through EEG signals (2019)
The design and implementation of a controlinterface by EEG signals which command allows horizontal,vertical movements of a cursor and clicking on 2-D is presented.The interface allows the acquisition, filtering, artifact removaland extraction of characteristics from the discrete wavelettransform. The search feature focuses on time domain parameters (P300) and the frequency domain (Beta Mu)depending on whether it is a visual stimulus or imaginationof movement, respectively. For identification, two stages ofclassification based on artificial neural networks are used,through which a 78.57% overall performance for horizontalmovement, 52.38% for the vertical movement and click 100%was obtained.